Pengaruh Online Customer Review dan Promotional Content pada Impulse Buying Produk Skincare The Originote di Platform Tiktok dengan Influencers sebagai Variabel Moderasi - Chamisyahuri, Chamisyahuri; Purmono, Bintoro Bagus; Jaya, Arman; Afifah, Nur; Setiawan, Harry (Lembaga Publikasi Ilmiah Nusantara, 2025)
The high public interest in skin care products has led to consumers facing various choices, encouraging manufacturers to innovate and promote their products, including through influencers. This study aims to evaluate the effect of online customer reviews and promotional content on impulse buying of The Originote products in Indonesia, with influencers as moderating variables. The focus of the study is Indonesian consumers aged 17 years and over who have purchased and tried The Originote products at least once. Data were collected through questionnaires from 205 respondents using purposive sampling techniques and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results showed that online customer reviews and promotional content have a positive and significant effect on impulse buying. However, influencers do not significantly moderate their relationship to impulse buying. This finding suggests that in digital marketing, trust in online customer reviews and the strength of promotional content are more effective in driving impulse buying than influencers. The practical implication of this research is the importance for businesses to focus marketing strategies on strengthening promotional content and online customer reviews